Developing the construct of student development using fuzzy delphi technique: A study on the undergraduates from vocational universities in Shandong, China - Xing, Qiaona (2024)
The main research content of this thesis is to develop the studentdevelopment construct of China’s undergraduate vocational universities and improve the quality of training high-quality tech talents in China. This thesis adheres to the problem-oriented approach and conducts four-stage research to solve the core problems of irrational talent construct, low training quality, and insufficient talent quantity in response to the existing issues in training high-quality tech talents in China. This thesis is based on undergraduate vocational education, student development theory, and expert opinions. Specifically, it designed the student development construct based on the implementation process of OBE theory. This thesis is a four-stage study: In the first stage, the researcher analyzed the necessity of student construct design by interviewing vocational education policymakers, undergraduate vocational university talent training goal makers, and students. At stage two, this thesis used the Fuzzy Delphi Technique (FDT) and Analytic Hierarchy Process (AHP) to design the undergraduate vocational education student development construct. In the third stage, evaluated the student development level. This thesis developed a student development instrument and evaluated student development level. At stage four, proposed countermeasures to improve student development level based on the differences between the evaluation results and student development outcomes. The research methods of this thesis include interviews, FDT, AHP, and questionnaire methods. The FDT was used to design the student development construct indexes, and the AHP was used to assign index weights. A stratified sampling method was used to select 1422 students from three undergraduate vocational universities in Shandong, China. This thesis designed a student development instrument and used the questionnaire to collect student development data. The SPSS (version 25) software was used to test the reliability and validity of the questionnaire and to analyze the collected student development questionnaire data to evaluate the student development level. The research value of this thesis includes: First, using Outcome-Based Education (OBE) theory in Chinese vocational education and student development will enrich the research results of student development theory and Chinese vocational education. Second, this thesis helps solve the problem of the shortage of high-quality tech talents in China and helps Chinese undergraduate vocational universities to improve the quality of student training. Third, this thesis is based on the OBE of student development quality, which provides new ideas for reforming China’s education quality evaluation.